Desenvolvimento de metodologia para implementação de eficiência energética em sistemas auxiliares de uma planta industrial siderúrgica semi-integrada - Pinto, Leandro Mendes [UNESP] (2016)
At present energy efficiency is one of the issues most frequently cited in industries, as companies that invest in energy efficiency projects can save resources, improve competitiveness and helps ease the pressure on increasing the supply of energy. Postpone part of the investment in increasing energy supply allows the government and the business owner to release resources for other priorities, without loss of quality, security of supply and social and environmental gains. This study presents application criteria of energy efficiency methodology in a steel industry which are evaluated in three areas of a steel mill, such as drive systems, thermal systems and lighting systems, where can be made significant gains by implementing the methodology of energy efficiency.